Supercritical carbon dioxide extraction of oil from Thunnus tonggol head by optimization of process parameters using response surface methodology - Ferdosh, Sahena; Sarker, Md. Zaidul Islam; Rahman, Nik Norulaini Nik Ab; Akand, Md Jahurul Haque; Ghafoor, Kashif; Awang, Mohamed Bin; Kadir, Mohd Omar Ab (Springer, 2013)
Total oil was extracted from ground fish head of Longtail tuna (Thunnus tonggol) using supercritical carbon dioxide (SC-CO2) at 20 to 40 MPa, 45 to 65 oC and 1 to 3 ml min−1. Response surface methodology (RSM) was employed to optimize the operating conditions of the SC-CO2 technique where the highest oil yield was obtained (35.6% on dry weight basis) at 40 MPa, 65 oC, and 3 ml min−1. The solubility of the oil in SC-CO2 increased from 2.9 to 14.2 g oil/100 g of CO2 with increasing pressure and temperature. The total saturated, monounsaturated and polyunsaturated fatty acids obtained were 41.6, 24.7 and 26.8%, respectively, where the omega-3 fatty acids were found to be 22.3%. A correlation was developed determining the coefficients of the second-order polynomial equation where the extraction parameters of SC-CO2 method to extract fish oil from fish sample were successfully optimized using response surface methodology.